1996
DOI: 10.1002/(sici)1096-8628(19960712)64:1<209::aid-ajmg38>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X founder chromosomes in Italy: A few initial events and possible explanation for their heterogeneity

Abstract: A total of 137 fragile X and 235 control chromosomes from various regions of Italy were haplotyped by analyzing two neighbouring marker microsatellites, FRAXAC1 and DXS548. The number of CGG repeats at the 5′ end of the FMR1 gene was also assessed in 141 control chromosomes and correlated with their haplotypes. Significant linkage disequilibrium between some “major” haplotypes and fragile X was observed, while other “minor” haplotypes may have originated by subsequent mutation at the marker microsatellite loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 55 publications
5
33
4
Order By: Relevance
“…In agreement with other studies, [21][22][23][24][25][26][27][28][29] A-2 and D-6 were also highly prevalent in our sample (38% of patients), supporting the contention that these two haplotypes are present on ancestral European fragile X founder chromosomes. 28,29 The presence of haplotypes C-2 and C-5 in 16 (38%) fragile X chromosomes, suggests the existence of specific founder mutations in Portuguese patients, since no similar findings have been observed in other populations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other studies, [21][22][23][24][25][26][27][28][29] A-2 and D-6 were also highly prevalent in our sample (38% of patients), supporting the contention that these two haplotypes are present on ancestral European fragile X founder chromosomes. 28,29 The presence of haplotypes C-2 and C-5 in 16 (38%) fragile X chromosomes, suggests the existence of specific founder mutations in Portuguese patients, since no similar findings have been observed in other populations.…”
Section: Discussionsupporting
confidence: 93%
“…28,29 The frequency of haplotype C-7 in normal chromosomes was significantly higher than that expected from the corresponding allele frequencies. This finding may indicate the existence of linkage disequilibrium between the two markers and/or the selective advantage of this haplotype when associated with the normal FMR1 gene as compared to C-7 fragile X chromosomes.…”
Section: Discussionmentioning
confidence: 74%
“…The DXS548 polymorphism was detected by a modified PCR method (Riggins et al, 1992) using primers described by Chiurazzi et al (1996a). Consistency of allele denomination was ensured by typing control DNAs kindly provided by Dr JN Macpherson (Salisbury Hospital, Salisbury, England) and by Dr K Grnskov (The John F Kennedy Institute, Glostrup, Denmark).…”
Section: Dna Analysesmentioning
confidence: 99%
“…DXS548 (Riggins et al, 1992) and FRAXAC1 , two dinucleotide (CA) repeat markers 150 and 7 kb, respectively, proximal to the CGG repeat, have been the most characterized marker loci used in association studies. Haplotype construction with these markers has revealed linkage disequilibrium between the normal, stable alleles as well as the unstable CGG repeat alleles among individuals with fragile X syndrome in studies of European populations from France and Spain (Oudet et al, 1993a), Belgium and the Netherlands (Buyle et al, 1993), Northern Europe (Riggins et al, 1992), Italy (Chiurazzi et al, 1996a), United Kingdom (Macpherson et al, 1994), Sweden (Malmgren et al, 1994), Finland (Oudet et al, 1993b;Haataja et al, 1994;Zhong et al, 1996), Greece and Cyprus (Patsalis et al, 1999) and Denmark (Larsen et al, 1999(Larsen et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…No trend in this direction was observed, since the distribution of the haplotypes in premutation women with POF did not characterize their families as a subset of fragile X families. Indeed, 60% of the premutation carriers with POF had the haplotypes most commonly observed on the fragile X chromosomes in Brazilian families as well as in other populations (Chiurazzi et al, 1996). Therefore, no indication was found that the POF-associated premutations had a specific origin or resided on a particular haplotype background.…”
Section: Discussionmentioning
confidence: 98%